Accounting and control in the system of marketing and logistics support for Ukrainian wineries - Uliana Marchuk; Liubov Gutsalenko; Svitlana Rybalchenko; Serhiy Zabolotnyy (Accounting and Financial Control)
Effective winery management requires the systematic integration of accounting data, logistics information, and digital marketing elements. The paper explores conceptual approaches to integrating the accounting and control systems with marketing and logistics processes in Ukraine’s winemaking industry within the context of digital transformation. Based on the results of the software market analysis, the advantages and limitations of various types of software (ERP, CRM, QR marking, RFID, etc.) for Ukrainian wineries are summarized. Critical factors for the successful implementation of digital technologies have been identified, such as technological readiness of an enterprise, availability of qualified personnel, financial capacity, and adaptability of systems to Ukrainian market conditions. The functional significance of organoleptic control in the system of internal quality monitoring is determined, specifically in identifying signs of counterfeiting and ensuring product compliance with established standards. The study proposes a logical and functional model of synergy of digital accounting, marketing, and logistics, enabling strategic control based on real-time data. It also presents IT solution implementation scenarios adapted to the scale of a winery’s operations, its digital maturity, and business priorities. The study results have practical significance for enhancing management decisions, optimizing quality control, improving the efficiency of sales channels, and fostering consumer trust in the brand.